Characteristics of Clinical Signs in the Comorbid Course of Allergic Rhinitis and Bronchial Asthma in Children (International Journal of Scientific Pediatrics, 2026)
Introduction. Allergic rhinitis and bronchial asthma are among the most common allergic diseases in children and are pathogenetically interrelated. The comorbid course of these diseases may lead to more severe clinical manifestations, difficulties in disease control, and a reduction in patients’ quality of life. The aim of the study was to investigate the characteristics of clinical signs in children with allergic rhinitis comorbid with bronchial asthma. Materials and methods. The study was conducted at the Department of Pediatric Allergology of the multidisciplinary clinic of Tashkent State Medical University. The age of the examined patients ranged from 7 to 18 years, with a mean age of 10.1 ± 0.31 years. Group 1 included 100 children with comorbid allergic rhinitis and bronchial asthma. Group 2 included 50 children with allergic rhinitis, of whom subgroup 2a consisted of 24 patients with intermittent allergic rhinitis (IAR), and subgroup 2b consisted of 26 patients with persistent allergic rhinitis (PAR). The main clinical symptoms, their frequency, severity, and interrelationships were analyzed in children with allergic rhinitis and bronchial asthma. Results and discussion. Nasal obstruction was identified in 72 patients (72%) in Group 1 with combined allergic rhinitis and bronchial asthma, in 15 patients (62.5%) in subgroup 2a with intermittent allergic rhinitis, and in 17 patients (65.3%) in subgroup 2b with persistent allergic rhinitis (p
Keywords: children; allergic rhinitis; bronchial asthma; comorbidity; clinical signs; allergic diseases; symptoms; diagnosis